Survey on Onboarding Software Engineers During a Pandemic - Rodeghero, Paige; Zimmermann, Tom; Ford Robinson, Denae (Microsoft, 2020)
This technical report includes a Microsoft Research survey that was deployed to new software engineering hires to learn about their onboarding experience during the COVID-19 pandemic.